Poor cell block adequacy rate for molecular testing improved with the addition of Diff‐Quik–stained smears: Need for better cell block processing. Issue 8 (8th May 2015) - Harada, Shuko; Agosto‐Arroyo, Emmanuel; Levesque, Jessica A.; Alston, Evan; Janowski, Karen M.; Coshatt, Gina M.; Eltoum, Isam A.
<x xml:space="preserve">Abstract</x> BACKGROUND In the era of personalized medicine, requests for molecular testing of specimens obtained with minimally invasive procedures such as fine‐needle aspiration have been increasing. Although cell blocks (CBs) are the recommended specimens for molecular testing, their performance has not been well analyzed. The objective of this study was to assess the frequency and types of samples deemed unsatisfactory for molecular testing (quantity not sufficient [QNS]). METHODS One year after the implementation of careful monitoring of QNS cases, cases submitted for lung cancer molecular testing were analyzed for the QNS rate. When the cases were rejected for the inadequacy of CBs of cytology specimens, air‐dried, Diff‐Quik (DQ)–stained smears were reviewed and used if they were adequate. The QNS rates were compared across 4 specimen categories: large resection, small biopsy, CB alone, and CB with DQ smears. RESULTS One hundred seventy‐six cases were studied, and 45 (25.6%) were unsatisfactory. Only 1 of 73 large resection specimens was rejected because of decalcification. The QNS rate for small biopsy specimens was 35.9% (28 of 78), whereas 64% (16 of 25) of cytology cases ordered on CBs were rejected. In combination with DQ smears, the QNS rate of cytology specimens was 32% (8 of 25), which was a significant improvement over CBs only (P = .024) and was not significantly different from the QNS rate for small biopsies (P = .671). CONCLUSIONS The utilization of DQ‐stained smears for molecular testing improves the adequacy of cytologic samples and provides a minimally invasive alternative to surgical biopsy when molecular analysis of tumor material is necessary. Cancer (Cancer Cytopathol) 2015;123:480–7. © 2015 American Cancer Society.